Development of a Professional 3D Pageflip Based E-Module on Radioactivity Material - Saputri, Ika; Imasari, Nyi (Program Magister Teknologi Pendidikan Universitas Jambi, 2016)
This research aims to determine the final product of a professional 3D Pageflip-based electronic module on radioactivity and nuclear reactions in the Atomic and Nuclear Physics course. This research is research and development research with a 4D development model. The stages in the 4D model development model are define, design, development, and disseminate. The research instruments used were observation, document review, student needs questionnaire, media expert validation questionnaire, and material expert validation questionnaire. Then the resulting data was analyzed using descriptive statistics. The resulting product has specifications including the final format of the program is exe, the program is equipped with colors, images, animation and video using Times New Romans font type, the module consists of an introductory, learning and closing section which includes material namely radioactivity and nuclear reactions and the level of media users, namely universities. The advantages of the electronic module include the language used which is easy to understand, the videos displayed are in 3D format, there is a separate answer sheet for answering practice questions and conclusions. Can be used remotely, students can see the scores obtained from the final test and can be used directly without having to have the application.